Boron-rich diet may regulate blood lipid profile and prevent obesity: A non-drug and self-controlled clinical trial - YARAT, AYŞEN; AKYÜZ, SERAP HATİCE (ELSEVIER GMBH, 2019)
Background: Boron is an element commonly found in nature. The main boron source for organisms is through food and drinking water. In recent years, it is suggested that the boron-rich diet can affect human health positively. However, more detailed studies are needed. Objective: The aim of this study was to examine the effect of increased dietary boron intake on some biochemical parameters in humans. Material and methods: Thirteen healthy women consumed diets containing 10 mg more boron than their routine diet for one month. This boron intake was provided with the increase of boron-rich foods such as dried fruits, avocado, and nuts in the diet. Some biochemical and hematologic parameters were determined in blood, urine and saliva samples taken before and after a boron-rich diet. Results: Serum, salivary, and urine boron concentrations increased 1.3, 1.7, 6.0 fold, respectively. The most significant clinically change was found in the lipid profile. Serum total, LDL, VLDL cholesterol, and triglyceride levels decreased significantly. Body weight, body fat weight, and Body Mass Index also decreased. Significant changes in serum TSH and salivary buffering capacity were also found. Conclusion: Increasing the intake of boron through dietary means might contribute to beneficial effects on lipid metabolism, obesity, and thyroid metabolism; salivary boron may reflect serum boron; and boron may be used as a cariostatic agent in dentistry. An increased intake of other dietary factors such as fiber, potassium, iron, vitamin A, and vitamin E in the boron-rich foods might have been responsible of the effects described. To our knowledge, this study is the first clinical study in which dietary boron intake is increased via foods.
Keywords: Diet; Boron; Serum; Saliva; Urine; Trace element; RISK-FACTORS; CALCIUM FRUCTOBORATE; BORIC-ACID; SUPPLEMENTATION; HEALTH; CHOLESTEROL; INHIBITION; METABOLISM; MAGNESIUM; ADEQUATE